Fellow creatures : our obligations to the other animals - Korsgaard, Christine M. (Christine Marion) (Uehiro series in practical ethics., 2018)
Christine M. Korsgaard presents a compelling new view of our moral relationships to the other animals. She offers challenging answers to such questions as: Are people superior to animals, and does it matter morally if we are? Is it all right for us to eat animals, experiment on them, make them work for us, and keep them as pets?